2017
DOI: 10.1007/s10551-017-3478-6
|View full text |Cite
|
Sign up to set email alerts
|

Do Board Secretaries Influence Management Earnings Forecasts?

Abstract: The role of board secretaries is a unique institutional feature in China. Individuals in this senior executive role are responsible for coordinating information disclosure. We study the impact of board secretaries on management earnings forecasts and find that their legal expertise, accounting expertise and foreign experience help improve management earnings forecast quality. The quality of forecasts, as indicated by their occurrence, frequency, precision and accuracy, is also positively associated with the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 67 publications
4
50
0
Order By: Relevance
“…It appears through the findings that IPO firms with separate CEO and chairman positions are not expected to issue accurate earnings forecasts, in that the agency theory's argument of separation of responsibilities is not supported. This is consistent with the result provided by Xing et al (2019), which revealed that board secretaries with dual roles are more capable of accessing information and resources, which ultimately results in providing high-quality management earnings forecasts. Table 3 also shows that management ownership (MOWN) has a negative and insignificant relationship with AFER, in that the higher the management ownership, the lower will be the earnings forecast error.…”
Section: Multivariate Regression Analysissupporting
confidence: 90%
“…It appears through the findings that IPO firms with separate CEO and chairman positions are not expected to issue accurate earnings forecasts, in that the agency theory's argument of separation of responsibilities is not supported. This is consistent with the result provided by Xing et al (2019), which revealed that board secretaries with dual roles are more capable of accessing information and resources, which ultimately results in providing high-quality management earnings forecasts. Table 3 also shows that management ownership (MOWN) has a negative and insignificant relationship with AFER, in that the higher the management ownership, the lower will be the earnings forecast error.…”
Section: Multivariate Regression Analysissupporting
confidence: 90%
“…To date, empirical studies related to company secretaries are set in China. However, Xing et al (2019) explain that board secretaries in China differ greatly from company secretaries in Western countries. Board secretaries are required by law to be present in top management teams in China and have a unique responsibility for coordinating information disclosure.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…While the literature on role of corporate governance is voluminous, the literature on the role of company secretaries is relatively descriptive or qualitative, given that we know that company secretaries perform an important role (Hocken and Latimer, 2006;Robertson, 2018). Studies find evidence on the various roles of company secretaries (Peij et al, 2015;Kakabadse et al, 2016;Xing et al, 2019;Wang et al, 2019); however, there is little empirical evidence on how the various roles are related to board and firm outcomes. Xing et al (2019) examine firms in China and note that company secretaries' expertise is related to the quality of management forecasts made by the firm, whereas Wang et al (2019) examine the effect of Chinese company secretaries' tenure on firm outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations